The longitudinal associations among perceived discrimination, social initiative, and depressive symptoms in Chinese rural left-behind adolescents. (June 2020) - Zhao, Jingxin; Wang, Qian; Xue, Xiangjuan
Abstract: Introduction: Perceived discrimination is a significant stressor in the lives of Chinese rural left-behind adolescents. Although some research has examined the effects of perceived discrimination on left-behind adolescents' psychosocial functioning, the majority of existing research is cross-sectional, which limits the understanding of the underlying mechanism of these effects. The current study used a longitudinal design to explore how perceived discrimination is associated with psychosocial functioning (i.e., depressive symptoms and social initiative) over time in Chinese rural left-behind adolescents. Methods: A total of 1011 rural left-behind adolescents (54% boys) were involved in an ongoing longitudinal study. At Time 1 ( M age = 12.93, SD = 0.86), adolescents completed measures of perceived discrimination, depressive symptoms, and social initiative. At Time 2 (one year later), adolescents again reported on their depressive symptoms and social initiative. Results: Perceived discrimination was concurrently and longitudinally associated with left-behind adolescents' depressive symptoms and social initiative. The effect of perceived discrimination on depressive symptoms was partially mediated by social initiative, while the effect of perceived discrimination on social initiative was fully mediated by depressive symptoms. The associations applied equally to adolescents with two migrant parents and adolescents with only a migrant father. Conclusions: These findings suggest the harmful impact of perceived discrimination on rural left-behind adolescents' social initiative and depressive symptoms and underscore the importance of eliminating discrimination in the rural left-behind adolescents' intervention program.